If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + 5) + -7 = 42 Reorder the terms: (5 + 3x) + -7 = 42 Remove parenthesis around (5 + 3x) 5 + 3x + -7 = 42 Reorder the terms: 5 + -7 + 3x = 42 Combine like terms: 5 + -7 = -2 -2 + 3x = 42 Solving -2 + 3x = 42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 3x = 42 + 2 Combine like terms: -2 + 2 = 0 0 + 3x = 42 + 2 3x = 42 + 2 Combine like terms: 42 + 2 = 44 3x = 44 Divide each side by '3'. x = 14.66666667 Simplifying x = 14.66666667
| 4(1+4n)=-124 | | 3x+6=4x-17 | | 27x+9y=54 | | 4x-6-9x+1=0 | | 8(x-6)=-88 | | -3x+36=-18 | | 6b^2+13b-63= | | 3/4*2/7= | | 8*9n=96 | | 19-(2x+3)=2(x+3) | | 2(x+1)=3x-15 | | 10y-2=3y+33 | | 3(5+4b)-2=0 | | 3z-4=5z-1 | | 4+a=16 | | 82=2(-1+7m) | | 7+3.2=3.2x | | 2b+8=0 | | 6y-4(2-3(4y-1))=-17 | | A+81=9z-7 | | 7b+13=35-4b | | 166=2*36+2W | | 27x^2+37x=0 | | 3=2(-2)-y | | 4x-12=3.5 | | 10+x=1x+2 | | 3(x+4)-2=3x+10 | | 2x-4y+-6=0 | | 6y+15=9y | | 2u+10=20 | | 3b*c= | | 2x^3-12x^2+24x-14=0 |